Outsourcing usług IT w sektorze bankowym na przykładzie rynku niemieckiego - Karagiannis, Dimitris; Kossowski, Michał; Junginger, Stefan; Krzysztoń, Ewa (Outsourcing of IT Services in the Banking Sector : the German Market Example, 2005)
In the last decades we could observe growing demands on IT services and their enormous development. In order to keep up with this IT revolution, banks are forced to develop complex and expensive IT departments. This can be very challenging, especially for corporate banks, which IT budgets are often relatively small, if compared to, for example, private banks. The latest changes in the Polish banking law made the outsourcing of IT services possible, thus allowing banks to gain profits from the effects of scale. These changes could also be observed in Germany where computing centres, since many years, have been providing IT services for corporate banks. Taking into consideration market similarities, we assume that the development of computing centres in Poland will follow the German scenario..
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 91-98